Sinergi Komunikasi Transformatif dan Kepemimpinan Transformasional dalam Membangun Motivasi Intrinsik Dosen di Perguruan Tinggi: Kajian Literatur Sistematik - Budiman, Nikolaus; Emilia Graciela Mega Taran; Ismail Nasar; Ahmad Walela (Papanda Publisher, 2025)
This study systematically synthesizes the relationship between transformative communication and transformational leadership in shaping the intrinsic motivation of lecturers in higher education. Using the Systematic Literature Review method based on the PRISMA protocol, a total of 46 articles from five reputable databases were analyzed to identify relevant conceptual patterns. The findings indicate that inspirational and empathetic leadership, when combined with reflective and participatory communication, is capable of fulfilling the three basic psychological needs in Self-Determination Theory: autonomy, competence, and relatedness, which are the foundation of intrinsic motivation. Nonverbal communication dimensions such as facial expressions, eye contact, and tone of voice have also been shown to strengthen perceptions of authenticity and emotional closeness between leaders and lecturers. This study offers an integrative conceptual framework that emphasizes the importance of synergy between leadership and communication as the basis for strengthening faculty motivation and building an inclusive, collaborative, and sustainable academic ecosystem.